Introduction to the principles and methods underlying the recovery of metagenome‐assembled genomes from metagenomic data. Issue 3 (9th June 2022) - Goussarov, Gleb; Mysara, Mohamed; Vandamme, Peter; Van Houdt, Rob
Abstract: The rise of metagenomics offers a leap forward for understanding the genetic diversity of microorganisms in many different complex environments by providing a platform that can identify potentially unlimited numbers of known and novel microorganisms. As such, it is impossible to imagine new major initiatives without metagenomics. Nevertheless, it represents a relatively new discipline with various levels of complexity and demands on bioinformatics. The underlying principles and methods used in metagenomics are often seen as common knowledge and often not detailed or fragmented. Therefore, we reviewed these to guide microbiologists in taking the first steps into metagenomics. We specifically focus on a workflow aimed at reconstructing individual genomes, that is, metagenome‐assembled genomes, integrating DNA sequencing, assembly, binning, identification and annotation. Abstract : Metagenomics greatly facilitates the identification and characterization of known and novel microorganisms. The plethora of available bioinformatics tools with various levels of complexity rely on (shared) fundamental principles and methods, which are often not detailed or scattered. Here, we review these principles and methods with a focus on reconstructing individual genomes from metagenomics data by integrating DNA sequencing, assembly, binning, identification and annotation.